Ethnobotanical Identification of Medicinal Plants Used by the Sangihe Tribe in Sangihe Archipelago District, North Sulawesi - A. Hadian Pratama Hamzah; Nurhasanah; Sri Harijati; Sinthia Brigyta Pangerapan; Cicik Suriani (Jurnal Penelitian Pendidikan IPA, 2023)
Ethnobotany is a field of science that studies the relationship between humans and plants. Ethnobotany is used by the community to document traditional knowledge such as the manufacture of traditional medicines obtained from generations of knowledge. Medicinal plants are extracted by hereditary methods by the Sangihe tribe which have medicinal properties. Sangihe is one of the large islands in the Sangihe and Talaud Islands group which stretches between the northern tip of Sulawesi Island and the southern tip of Mindanao Island in the Philippines. The use of medicinal plants by the people of Sangihe Regency has not been widely disclosed, so it is necessary to identify the medicinal plants used by the Sangihe tribe. The type of research used is explorative descriptive using research techniques in the form of exploration, the methods used are observation, interviews, documentation and plant inventory. The results obtained from this study are the use of plants as medicine by the Sangihe tribe, there are 29 species with 29 types of diseases. The use of medicinal plants by the Sangihe tribe is by boiling, drying or squeezing them by taking the extract from the water in the leaves. Medicinal plants used can also be eaten directly, smeared, mashed or mashed. The pattern of distribution of these plant species varies, growing in groups and also independently, scattered in several areas, even abroad.